Development and Validation of a Simple UV-Spectroscopic Method for the Estimate Metoprolol Tartrate in Bulk and Tablet Formulation - SG Vasantharaju (Journal of Global Pharma Technology, 2017)
Objective: UV-Spectroscopic method was developed and validated for quantitative determination of metoprolol tartrate. Method: The absorption maxima of metoprolol tartrate were found to be 223nm by using methanol as solvent. Results: The linearity range for metoprolol tartrate was 7-22μg/ml with correlation coefficient (r2) value 0.9982. The method was said to be accurate with 100% recovery and precise, robust as the %RSD was below 2. Metolar-50 marketed formulation was considered as test and assay was carried out. Assay was found to be 98.73%. Conclusion: So, a novel, simple and sensitive method was developed for assay of metoprolol tartrate and validated according to ICH Q2R1 guidelines.Keywords: Spectroscopic, Metoprolol tartrate, Absorption maxima, Assay.